Antioxidant and anticholinesterase activities of centella asiatica phenolic extract-mediated gold nanoparticles - Latif, Muhammad Sohail (2019)
In the present study, the green synthesis and optimization of gold nanoparticles (GNPs) using C. asiatica phenolic extract (CAP) were reported followed by the characterization with UV-vis, FTIR, Zeta potential, FESEM, EDX and XRD analyses. Total phenolic and flavonoid contents (TPC and TFC), antioxidant and anticholinesterase (anti-ChE) activities were also tested in vitro and Pearson correlation analysis was performed. The GNP synthesis using CAP was successfully accomplished under optimum conditions of reactants ratio of 1:1, 8 % CAP concentration, 0.5 mM HAuCl4 concentration and pH 9 at different temperatures of reaction medium (25 ℃, 40 ℃, 55 ℃ and 70 ℃). The results showed that the size range of GNPs was reduced from 6-40 nm at 25 ℃ to 6-30 nm at 40 ℃ and 55 ℃ while the sphericity of GNPs increased and the surface plasmon resonance (SPR) band became narrow. Although all GNP samples showed good antioxidant and anti-ChE activities (% I), the highest activity was recorded for the GNPs synthesized at 55 ℃, that is, 69.06 % and 76.72 % for ABTS and DPPH, and 71.71 % and 69.88 % for AChE and BChE, respectively, at the highest concentration of 500 μL sample. However, the maximum % I for ABTS and DPPH scavenging (79.76±1.01 and 75.51±1.54, respectively) was shown by ascorbic acid, and for AChE and BChE inhibition (75.18±2.29 and 79.94±1.11, respectively) by galanthamine. Pearson correlation analyses revealed a strong positive correlation between antioxidant activity and phenolic content as well as between anti-ChE and antioxidant activities for all GNP samples. The GNPs did not possess a significant cytotoxicity as shown by 20% mortality in brine shrimp lethality assay. The GNPs were haemocompatible as they induced 0.92 % haemolysis at the highest concentration (500 μL) in haemolysis assay compared to 99 % haemolysis by positive control. In conclusion, the results of this study show that CAP-GNPs possess good antioxidant and anticholinesterase activities, in addition to being non-cytotoxic and non-haemolytic, may be an option to further explore their therapeutic potential as antioxidant and cholinesterase inhibitors.